Analysis of financial security of business in a pandemic (Economics and region, 2021)
The article summarizes the theoretical approaches and proposes the solution of an important scientific problem, the formation and provision of financial security of business in a pandemic. The effects of COVID-19 are unlikely to have anything to do with what the world has seen so far, given the strength and speed with which the coronavirus has spread everywhere. In these circumstances, businesses should consider possible forms of forecasting the effects of the pandemic's economic impact on their activities. The problems of defining the economic essence of the concept of financial security of business are investigated. Destabilizing factors have been identified that negatively affect the financial condition of the business, which in turn leads to a decrease in the level of financial security. Methodological approaches to assessing the financial security of business are generalized, the considered methods of calculating indicators use critical or threshold values, within the deviation of which the necessary condition is the gradation of levels of financial security of business. A comparative and trend analysis of business financial security indicators was conducted and real threats to business financial security in Ukraine were identified, including a decrease in production and sales due to disruption of supply chains, sales or provision of services in the usual amounts due to quarantine restrictions. pandemic COVID-19, reducing the level of profitability of operating activities of enterprises, a sharp reduction in the number of registered businesses, rising unemployment and others. The impact of business development indicators in Ukraine on financial security has been modeled and the integrated dependence of the integrated index on net profit / loss of enterprises, sales volume and profitability of enterprises has been established. The development of business and ensuring its financial security targets in the context of the COVID-19 crisis will minimize the negative impact of current threats related to quarantine restrictions, both at the level of individual regions and the country as a whole.
Keywords: financial security; pandemic; risks; threats; modeling; ways to improve